Hysterectomy‐corrected cervical cancer mortality rates in Denmark during 2002‐2015: A registry‐based cohort study. (10th April 2019) - Hammer, Anne; Kahlert, Johnny; Gravitt, Patti E.; Rositch, Anne F.
Abstract: Introduction: We aimed to describe the cervical cancer mortality rates after correcting for hysterectomy and to evaluate trends over calendar time and by age. Material and methods: Using data from nationwide registries, we calculated uncorrected and hysterectomy‐corrected cervical cancer mortality rates among women age ≥20 years in Denmark during 2002‐2015. We calculated hysterectomy‐corrected rates by subtracting post‐hysterectomy person‐years from the denominator, unless hysterectomy was performed due to cervical cancer. Results: The age‐standardized hysterectomy‐corrected cervical cancer mortality rate of 5.8/100 000 was 18.4% higher than the corresponding uncorrected rate. The hysterectomy‐corrected cervical cancer mortality rate increased significantly with age, particularly in women aged 65+ (annual percent change +4.57), peaking at 26.1/100 000 person‐years in women aged ≥85. The hysterectomy‐corrected cervical cancer mortality declined significantly over calendar time, from 6.3/100 000 person‐years in 2002 to 4.5/100 000 person‐years in 2015 (annual percent change −0.22). This was mainly due to a significant decline in women aged 60 years and older, from 20.4/100 000 person‐years in 2003 to 9.3/100 000 person‐years in 2015 (annual percent change −0.75). Conclusions: The mortality of cervical cancer increased significantly by age, particularly among women aged 65 years and older for whom routine cervical cancer screening is not recommended. Understanding reasons for the high mortality rate in older women is critical, as this may help identify interventions needed to ensure a continued decline in cervical cancer mortality in older Danish women.